Silicon Enhances Antioxidant Capacity and Photochemical Efficiency in Drought-Stressed Creeping Bentgrass (Agrostis stolonifera L.) Putting Greens - Xunzhong Zhang; Travis Roberson; Mike Goatley; Taylor Flanary; David McCall (Horticulturae, 2025)
Creeping bentgrass (Agrostis stolonifera L.) is an important cool-season turfgrass species that is not well understood. The objective of this study was to determine the effects of the mechanisms underlying silicon (Si) on creeping bentgrass drought tolerance under field conditions from 2022 to 2023. Five treatments, including a control (potassium silicate at 0.95 and 1.90 mL m−2), Dyamin-OSA at 0.64 and 1.28 mL m−2, and Agsil 21 at 0.35 mL m−2, were arranged in a randomized block design with four replications and applied biweekly to creeping bentgrass putting greens during summer months. Deficit irrigation was applied to induce drought stress in June and July. The Si treatments exhibited beneficial effects on turf quality, physiological fitness, and root viability. K-silicate at 1.90 mL m−2 and Agsil 21 at 0.35 mL m−2 increased the leaf Si content by 32.0% and 22.8%, respectively, when compared to the control, as measured at the end of the trial. Among the treatments, K-silicate at 1.90 mL m−2, Dyamin-OSA at 0.64 mL m−2, and Agsil 21 at 0.35 mL m−2 tended to have greater beneficial effects than other Si treatments. Exogenous Si may improve drought tolerance by enhancing root growth and viability, Si uptake by roots, and antioxidant capacity and by protecting photosynthetic function.